2019
DOI: 10.1002/cplu.201900226
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolopyrrole Aza‐BODIPY Analogues as Near‐Infrared Chromophores and Fluorophores: Red‐Shift Effects of Substituents on Absorption and Emission Spectra

Abstract: Pyrrolopyrrole aza‐BODIPY analogues (PPABs) are a new class of UV/vis and near‐infrared chromophores. Varying the substituents results in red‐shifts of both the absorption and emission spectra. Extension of the lengths of the oligothiophene substituents from thiophene to quaterthiophene caused red‐shifts of the absorption and emission from 699 and 712 nm to 809 and 853 nm, respectively. The piperidylthiophene‐substituted PPAB exhibited similar red‐shifts of the absorption and emission to 810 and 831 nm, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Four-coordinate organoboron compounds with the rigid ligand often show good photoluminescence (PL) quantum yields and high hole and/or electron mobility. Boron coordination can improve molecular rigidity and planarity which lead to functional luminescent materials. The coordination potentially lowers the energy level of the lowest unoccupied molecular orbital (LUMO) because of the interaction between a lone pair of a nitrogen atom and a vacant p-orbital of a boron atom. , Kawashima et al reported that by forming a N–B coordination with azobenzene, the resulting complexes showed intense fluorescence. It is clarified that fluorescence can be induced by intramolecular N–B interaction which inhibits photoisomerization at the azobenzene scaffold and allowed the electronic transition related to emission.…”
Section: Introductionmentioning
confidence: 99%
“…Four-coordinate organoboron compounds with the rigid ligand often show good photoluminescence (PL) quantum yields and high hole and/or electron mobility. Boron coordination can improve molecular rigidity and planarity which lead to functional luminescent materials. The coordination potentially lowers the energy level of the lowest unoccupied molecular orbital (LUMO) because of the interaction between a lone pair of a nitrogen atom and a vacant p-orbital of a boron atom. , Kawashima et al reported that by forming a N–B coordination with azobenzene, the resulting complexes showed intense fluorescence. It is clarified that fluorescence can be induced by intramolecular N–B interaction which inhibits photoisomerization at the azobenzene scaffold and allowed the electronic transition related to emission.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding excitation peak has also changed (Figure S11). Similarly, the absorption of Cu-Pc-CDs in the Soret band at 370 nm is redshifted (about 45 nm) compared with that of Cu-Pc, demonstrating the formation of new chromophores (Figure e) . What is particularly interesting is that the Q absorption band at the visible-light region (732 nm) disappears, avoiding light absorption losses of the PVK layer .…”
Section: Resultsmentioning
confidence: 86%
“…Further elongating the thienyl numbers at the α‐positions to red‐shift absorption was demonstrated in their later report. [ 126 ] Moreover, upon cutting the fused heterocycles and the α‐aromatic substituents, significantly changed energy levels and bandgaps were observed. It worth to note that these B‐complexed DPP molecules (63‐70) showed low‐lying LUMOs of −3.8–−3.5 eV, suggesting strong electron affinity and potential electron‐transport properties.…”
Section: B←n‐bridged Conjugated Unitsmentioning
confidence: 99%